Partially oxidized polyvinyl alcohol as a promising material for tissue engineering. (29th October 2015) - Stocco, Elena; Barbon, Silvia; Grandi, Francesca; Gamba, Pier Giorgio; Borgio, Luca; Del Gaudio, Costantino; Dalzoppo, Daniele; Lora, Silvano; Rajendran, Senthilkumar; Porzionato, Andrea; Macchi, Veronica; Rambaldo, Anna; et al.
Abstract: The desired clinical outcome after implantation of engineered tissue substitutes depends strictly on the development of biodegradable scaffolds. In this study we fabricated 1% and 2% oxidized polyvinyl alcohol (PVA) hydrogels, which were considered for the first time for tissue‐engineering applications. The final aim was to promote the protein release capacity and biodegradation rate of the resulting scaffolds in comparison with neat PVA. After physical crosslinking, characterization of specific properties of 1% and 2% oxidized PVA was performed. We demonstrated that mechanical properties, hydrodynamic radius of molecules, thermal characteristics and degree of crystallinity were inversely proportional to the PVA oxidation rate. On the other hand, swelling behaviour and protein release were enhanced, confirming the potential of oxidized PVA as a protein delivery system, besides being highly biodegradable. Twelve weeks after in vivo implantation in mice, the modified hydrogels did not elicit severe inflammatory reactions, showing them to be biocompatible and to degrade faster as the degree of oxidation increased. According to our results, oxidized PVA stands out as a novel biomaterial for tissue engineering that can be used to realize scaffolds with customizable mechanical behaviour, protein‐loading ability and biodegradability. Copyright © 2015 John Wiley & Sons, Ltd.